2007
DOI: 10.1029/2006wr005679
|View full text |Cite
|
Sign up to set email alerts
|

Tide‐induced recirculation across the aquifer‐ocean interface

Abstract: [1] A parametric analysis is conducted to examine the influence of tides, inland hydraulic conditions, and aquifer properties on the rate of tide-induced seawater recirculation through the nearshore aquifer. Understanding such influence is crucial for accurate prediction of subsurface chemical fluxes to coastal waters via groundwater discharge. The analysis is based on numerical simulations of density-dependent groundwater flow in a coastal aquifer subject to tidal oscillations across a sloping beach face. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
145
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(156 citation statements)
references
References 73 publications
11
145
0
Order By: Relevance
“…Numerical modeling demonstrated that a net southward flowing coastal current transported this highly radioactive seawater along the shoreline (11). We hypothesize that seawater intrusion, driven in part by waves and tides (12)(13)(14)(15), led to the storage of 137 Cs by adsorption onto beach sands. In the years since the accident, falling ocean 137 Cs activities and similar groundwater-surface water exchange processes would have led to the reverse reaction (desorption) and the elevated beach groundwater 137 Cs activities observed today (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Numerical modeling demonstrated that a net southward flowing coastal current transported this highly radioactive seawater along the shoreline (11). We hypothesize that seawater intrusion, driven in part by waves and tides (12)(13)(14)(15), led to the storage of 137 Cs by adsorption onto beach sands. In the years since the accident, falling ocean 137 Cs activities and similar groundwater-surface water exchange processes would have led to the reverse reaction (desorption) and the elevated beach groundwater 137 Cs activities observed today (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The challenge with this classification system is that there is currently no simple approach to predict tide-induced SGD rates. Robinson et al [2007c] presented a non-dimensional analysis to evaluate how various parameters impact tideinduced SGD for homogeneous, isotropic CUAs; however, the number of simplifications made in this study is likely to limit the general applicability of the findings. Information on the numerical simulations is provided in Robinson et al [2007b].…”
Section: Tidesmentioning
confidence: 99%
“…Field and numerical studies quantified the tidal effect on SGD and showed that tide-induced recirculation can represent a major portion of total SGD [e.g., Li et al, 1999;Taniguchi, 2002;Robinson et al, 2007c;Li et al, 2009]. Seawater infiltration into an aquifer occurs on the rising tide and exfiltration (saline SGD) on the ebbing tide [Robinson et al, 1998;Sholkovitz et al, 2003;Robinson et al, 2007c]. As a nearshore aquifer is able to fill faster than it can drain, infiltration is greatest from the mid-tide to high tide mark and exfiltration is greatest towards the low tide mark [Robinson et al, 2007b].…”
Section: Tidesmentioning
confidence: 99%
“…One important finding of studies of nearshorescale phenomena, which has only recently been well documented and modeled (Michael et al 2005;Robinson et al 2006Robinson et al , 2007Li et al 2008), was that nearshore systems with significant tides tend to form shallow saline recirculation cells. These cells are flushed with saline seawater over periods of hours to days and tend to result in a displacement toward deeper water of the lower part of the fresh seepage face by several meters.…”
Section: Nearshore Scalementioning
confidence: 99%
“…For example, many important aspects of shallow coastal aquifers and their interactions with the coastal ocean are transient and cannot be usefully approximated by steady-state assumptions. These phenomena would include influences of sea-level fluctuations due to tides, waves, and storms (Robinson et al 2006(Robinson et al , 2007Li et al 2008). They would also include water table fluctuations due to seasonal variations in recharge and evapotranspiration as well as during recharge pulses caused by heavy rainfall (Smith et al 2008) or rapid snow melt, or disturbance by sustained onshore pumping (McAuley et al 2001;Foyle et al 2002).…”
Section: Introductionmentioning
confidence: 99%